2004
DOI: 10.1073/pnas.0402156101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic profiles of p300 occupancy in vivo predict common features of promoter structure and coactivator recruitment

Abstract: Understanding the language encrypted in the gene regulatory regions of the human genome is a challenging goal for the genomic era. Although customary extrapolations from steady-state mRNA levels have been effective, deciphering these regulatory codes will require additional empirical data sets that more closely reflect the dynamic progression of molecular events responsible for inducible transcription. We describe an approach using chromatin immunoprecipitation to profile the kinetic occupancy of the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…Cells were stimulated with 1 M ionomycin (Calbiochem) and 50 ng/mL PMA (Sigma-Aldrich) at indicated time points as previously described (5). Cells were then fixed in 1% formaldehyde for 5 min and subjected to ChIP analysis as previously described (6). The complete protocol is provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were stimulated with 1 M ionomycin (Calbiochem) and 50 ng/mL PMA (Sigma-Aldrich) at indicated time points as previously described (5). Cells were then fixed in 1% formaldehyde for 5 min and subjected to ChIP analysis as previously described (6). The complete protocol is provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies from our group showed that p300 associates rapidly with the promoters of several genes in Jurkat human T cells following mitogen stimulation with phorbol ester and ionomycin (P/I) (5,6). We expanded this observation using ChIP-chip strategies and qChIP to profile genome-wide changes in promoter occupancy of p300 and pol II 45 min following mitogen stimulation ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, ChIP assays using an anti-p300 mAb to examine the kinetics of the association of p300 with multiple promoter regions in activated T cells revealed a class of promoters with common patterns of p300 recruitment. These also share aspects of gene-regulatory control and present evolutionarily conserved features of promoter structure [72].…”
Section: Cytokine-driven Stat Activation Constitutes a Secondary Thrementioning
confidence: 99%
“…10 In higher eukaryotes, most promoters and gene-regulatory regions are comprised of an integrated network of modular or 'composite' TF-binding sites (TFBS) [10][11][12] whose specific arrangement determines the expression specificity of the gene(s). A set of distinct TFBS that make up a regulatory constituent is called a cis-regulatory module.…”
Section: Introductionmentioning
confidence: 99%